A Functional Genomic Fingerprint of Chronic Stress in Humans: Blunted Glucocorticoid and Increased NF-κB Signaling - Miller, Gregory E.; Chen, Edith; Sze, Jasmen; Marin, Teresa; Arevalo, Jesusa M.G.; Doll, Richard; Ma, Roy; Cole, Steve W. (Biological psychiatry (1969), 2008)
Chronic stressors are known to increase vulnerability to medical illness, but the mechanisms underlying this phenomenon are poorly understood. To identify transcriptional control pathways that are modified by chronic stress, we conducted genomewide expression microarrays on familial caregivers of brain-cancer patients (n = 11) and matched control subjects (n = 10). Analyses were conducted on peripheral blood monocytes, which are cells that have the ability to initiate and maintain many inflammatory responses. Salivary cortisol was collected over the course of 3 days as volunteers went about normal activities. Caregivers' patterns of cortisol secretion were similar to those of matched control subjects. However, their monocytes showed diminished expression of transcripts bearing response elements for glucocorticoids, and heightened expression of transcripts with response elements for NF-κB, a key pro-inflammatory transcription factor. Caregivers also showed relative elevations in the inflammatory markers C-reactive protein and interleukin-1 receptor antagonist. These findings suggest that even in the absence of excess adrenocortical output, stress brings about functional resistance to glucocorticoids in monocytes, which enables activation of pro-inflammatory transcription control pathways. This persistent activation of inflammatory mechanisms may contribute to stress-related morbidity and mortality.